Density Dependence Shapes Life‐History Trade‐Offs in a Food‐Limited Population - Harman Jaggi; Wenyun Zuo; Rosemarie Kentie; Jean‐Michel Gaillard; Tim Coulson; Shripad Tuljapurkar (Ecology Letters, 2024)
Quantifying trade‐offs within populations is important in life‐history theory. However, most studies focusing on life‐history trade‐offs focus on two traits and assume trade‐offs to be static. Our work provides a framework for understanding covariation among multiple traits and how population density influences the traits. Using detailed individual‐based data for Soay sheep, we find density strongly shapes life‐history trade‐offs and distribution of lifetime reproductive success (LRS). At low density, a trade‐off between juvenile survival and growth structures life‐history variation, whereas at equilibrium density, trade‐off between reproduction and juvenile survival is the major structuring axes. Contrary to Lomnicki's prediction, we find that at high density, there is little variation in the LRS over the sizes (large juveniles and adults) that contribute to reproduction. Our results advance an understanding of dynamic nature of trade‐offs offer insights into how high‐density limits diversity of individual life histories and have implications for evolution via density‐dependent selection.